Development of a solar magnetic mendocino energy engine for studing for energy alternatives - Estupiñan, Cristian Mauricio
Thanks to photovoltaic cell development in 1953, it could be demonstrated that the use of light could have practical purposes. Later Calvin Fuller and Daryl Chaplin improved and proposed alternative uses for solar cells. The Mendocino Motor was one of those experimental issues in 1962. However, it was named by Larry Spring, who in 1994 at Mendocino Coast Labs implemented into his prototype a brushless maglev system to reduce friction of the concept. The engine became driven by sunlight and magnetic induction, using neodymium magnets located inside and outside the motor, equidistant locations from each other, in order to achieve magnetic force required to spin the rotor. Although there have been some scholars worldwide progress today, this field requires technological appropriation by students in Bucaramanga and Colombia, so that they get conscious about role that alternative energy for future, and how they can consider different uses for it. The general methodology is proposed projects and training by STEM (Science, Technology, Engineering, and Mathematics). The overall objective of the research is to design, build, simulate and prototype engine one Mendocino study and research, using the virtual modeling software “solidworks” and 3D printing tool Wanhao Duplicator i3. This research is descriptive, seeking to measure variables affecting engine performance through hardware platform Arduino. Due to complexity of this project, the research team is on phase to build and improve the prototype, with some pieces already printed or acquired, achieving levitation and stabilization of the rotor, so this project is under development yet.